DINAMIKA PANCASILA SEBAGAI DASAR NEGARA DAN IMPLEMENTASINYA - Fina Nurhaliza; Irsyad Bagus Satria; Media Rahmah; Anna Sari Hasibuan; Bambang Trisno (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract.This article aims to know and understand more about the dynamics of Pancasila as the basis of the state, understand the implementation of Pancasila, and understand the implementation of Pancasila values ​​in statutory regulations. This research method uses qualitative research methods and a descriptive approach. This method was chosen because it is the most appropriate method. This method is a research technique used to collect, analyze and interpret information obtained from various written sources, such as books, journals, articles, research reports and other documents relevant to the topic at hand. being researched. With the importance of Pancasila as the basis of the state, the author is interested in re-analyzing the dynamics of Pancasila as the basis of the state.